Spectral Violence: Art and Disappearance in Post-Ayotzinapa Mexico - Barriendos, Joaquin (PORTO ARTE: Revista de Artes Visuais, 2018)
In Mexico, memory has become a battlefield nowadays. The Ayotzinapa case (2014) –a still unresolved State-level human rights violation, including the disappearance of 43 students– transformed the public space into a permanent struggle between governmental amnesia and the politics of truth. With the emergence of various massive clandestine graves all across the country, a new form of violence emerged, characterized by the spectral materiality of the absent body. In this article, I elaborate on the relation between disappearance, social memory, and creative activism in recent Mexican art. Using the investigations of Forensic Architecture in Mexico as a case study, the text discusses the role of visual culture in the articulation of what I call the performativity of human rights. Resumo No México contemporâneo, a memória virou um campo de batalha. O caso Ayotzinapa (2014) –uma violação de direitos humanos orquestrada pelo Estado e ainda não resolvida, incluindo a situação de 43 estudantes ainda desaparecidos– transformou o espaço público em uma luta permanente entre a amnésia governamental e as políticas da verdade. O surgimento de fossas comuns clandestinas em todo o país propiciou também uma nova forma de violência caracterizada pela materialidade espectral do corpo ausente. O artigo pesquisa a relação entre desaparecimento, memória social e ativismo criativo na arte mexicana recente. Usando as investigações da Forensic Architecture no Mexico como estudo de caso, vamos analisar o papel da cultura visual na articulação do que o autor descreve como a performatividade dos direitos humanos.